Effectiveness Of The Printing Service For Teko Deso (Cak Ngateso) Applications In Balongbesuk Village - Rizky Nizar Wahyu Illahi; Widiyarta, Agus (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze and describe the effectiveness of the Cetak Pengajuan Teko Deso (Cak Ngateso) service in Balongbesuk Village, Diwek Subdistrict, Jombang District. Cak Ngateso is a web-based administrative service innovation launched by the Population and Civil Registration Office of Jombang Regency since 2021, focusing on services such as Family Cards, birth certificates, and death certificates at the village level. This study employs a qualitative method with a case study approach. Data was collected through interviews, observations, and documentation, then analyzed using Richard M. Steers' organizational effectiveness model, which includes indicators of goal optimization, system perspective, and pressure on behavior.The research findings indicate that, overall, the Cak Ngateso service in Balongbesuk Village has been effective in facilitating residents in processing population documents without having to visit the Population and Civil Registration Office. This is evidenced by the increasing number of service users each year and the village apparatus's ability to operate the system. However, there are still technical challenges such as server disruptions and infrastructure limitations that can hinder the service process.This study recommends enhancing human resource capacity, improving technological infrastructure, and optimizing the system to ensure that Cak Ngateso's services can operate more stably and reach all villages in Jombang District. Keywords: service effectiveness, Cak Ngateso, population administration,